Pembinaan Anti Korupsi dalam Keluarga Kristen dan Muslim di Kota Ambon - Resa Dandirwalu (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
This research focuses on the method of anti-corruption practiced by the Christians and Moslems family in Ambon, using qualitative analysis. The result shows that the cultivating method of anti-corruption which is used in the Christians and Moslems family in Ambon is still giving advice only. I suggest the reciprocal method as an alternative for the Christians and Moslems family in Ambon to cultivate the anti-corruption. There some steps of the reciprocal process, i.e., parents firstly give the understanding to the children, they then can make their questions in a dialog. The children will be given an opportunity to identify the corruption problem, and the new question will arise and then produce an idea that can be developed and practiced. Both parents and children finally are asked to keep away from the corruption. It will be one of the solutions to the Christians and Moslems family to avoid the corruption.